Equilibrium Long-Term Labor Contracts - Holmstrom, Bengt (Quarterly Journal of Economics, 1983)
The paper presents a labor market equilibrium analysis of implicit contract theory. A two-period, single-good model is used to propose consistent notions of labor market equilibrium for long-term employment contracts both when labor is specialized and cannot move in the second period and when there is free mobility without costs. The result that long-term contracts emerge in equilibrium even without mobility costs is novel and contrary to common beliefs. The main features of equilibrium are that (risk-neutral) firms will insure (risk-averse) workers against downside risk, yielding downward rigid wages. Wages are not fully rigid (as in earlier work on contract theory) because workers may quit and wages have to be bid up to retain them. The firm gets its return of the insurance deal by paying less than marginal product in the first period. The resulting equilibrium is second best and lies between productive efficiency and full insurance. Workers gain from long-term contracts in comparison to spot markets; whereas owners may not. In the model with specialized skills there exist transfer payments such that both parties are better off within an equilibrium with long-term contracts.